Evaluation Of Educational Service Quality At An Integrated Islamic Junior High School In Gowa Regency - A. Mutmainnah Taslim; Sitti Hajar; Wahyuni Adam (Indonesian Journal of Educational Science (IJES), 2025)
This study aims to examine the quality of educational services and to identify the priority factors for improving educational services at an Integrated Islamic Junior High School (SMP IT) in Gowa Regency. The research employed a quantitative method with a descriptive approach. The population consisted of all students at the selected SMP IT in Gowa Regency, with the entire population of 53 students taken as the sample. The data obtained were analyzed using Importance Performance Analysis (IPA) with the assistance of SPSS version 26. The findings indicate that the educational services experienced by the students are generally aligned with their expectations, as reflected in the average conformity level of 93.08%. Furthermore, three factors were identified as priorities for service improvement based on students perspective: teachers’ punctuality in attending scheduled classes (assurance dimension), the sincerity of mentors in caring for students during illness (empathy dimension), and the availability of textbooks or learning modules for students (tangible dimension). Based on these results, it is recommended that the school administration pay greater attention to the services provided to students as service users by improving the identified priority areas and maintaining the quality of services that are already satisfactory.